The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1365-313x.2012.04979.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis SYN3 cohesin protein is important for early meiotic events

Abstract: SUMMARY a-Kleisins are core components of meiotic and mitotic cohesin complexes. Arabidopsis contains four genes that encode a-kleisin proteins: SYN1, SYN2, SYN3 and SYN4. SYN1, a REC8 ortholog, is essential for meiosis, while SYN2 and SYN4 appear to be SCC1 orthologs and function in mitosis. SYN3 is essential for megagametogenesis and is enriched in the nucleolus of meiotic and mitotic cells. In this study the role of SYN3 during meiosis was investigated by characterization of plants that express SYN3-RNAi co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 84 publications
3
29
0
Order By: Relevance
“…They facilitate long-distance DNA interactions (Dorsett and Merkenschlager, 2013) and have been shown to affect long-range interactions between binding sites of the transcriptional repressor CTCF in a number of genes in animal cells (Bonora et al, 2014). Consistent with this, alterations in cohesin protein levels can result in tissue-specific alterations in transcript levels for a number of genes in Arabidopsis (this study; Yuan et al, 2012;Bolaños-Villegas et al, 2013;Liu and Makaroff, 2015). For example, transgenic plants expressing a pro35S:AtCTF7ΔB construct and ctf7 plants contain elevated levels of transcripts for epigenetically regulated transposable elements, including MU1, COPIA 28, and solo LTR, and alterations in transcript levels of several small interfering RNA-associated genes (Bolaños-Villegas et al, 2013;Liu and Makaroff, 2015).…”
Section: Ctf7 and Wapl Are Essential For Embryo Development But Not supporting
confidence: 54%
“…They facilitate long-distance DNA interactions (Dorsett and Merkenschlager, 2013) and have been shown to affect long-range interactions between binding sites of the transcriptional repressor CTCF in a number of genes in animal cells (Bonora et al, 2014). Consistent with this, alterations in cohesin protein levels can result in tissue-specific alterations in transcript levels for a number of genes in Arabidopsis (this study; Yuan et al, 2012;Bolaños-Villegas et al, 2013;Liu and Makaroff, 2015). For example, transgenic plants expressing a pro35S:AtCTF7ΔB construct and ctf7 plants contain elevated levels of transcripts for epigenetically regulated transposable elements, including MU1, COPIA 28, and solo LTR, and alterations in transcript levels of several small interfering RNA-associated genes (Bolaños-Villegas et al, 2013;Liu and Makaroff, 2015).…”
Section: Ctf7 and Wapl Are Essential For Embryo Development But Not supporting
confidence: 54%
“…8). Overexpression of cohesin proteins affects meiotic cell division in Arabidopsis (Yuan et al, 2012). Therefore, we established lines expressing kleisin subunits under the control of the ABI3 promoter, which has a relatively low and localized activity (Ng et al, 2004).…”
Section: Atscc4 Is Essential For Plant Cohesin Immobilization In the mentioning
confidence: 99%
“…The Arabidopsis genome encodes four kleisin subunits (Fig. 1A): the meiosis-specific SYN1 (Cai et al, 2003) and SYN3, involved in gene expression of meiotic genes, but also expressed in somatic cells (Yuan et al, 2012;Jiang et al, 2007), and SYN2 and SYN4, which have been suggested to participate in mitotic cell division (da Costa-Nunes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies point to SYN3 acting as a significant player during female meiosis [Yuan et al, 2012]. In SYN3 RNAi plants, male gametogenesis is only slightly affected, with a marginal reduction in pollen viability [Yuan et al, 2012]. Yet, these plants have significantly reduced fertility, resulting from the abortion of megaspore mother cells [Yuan et al, 2012].…”
Section: Sex-specific Cohesins In Arabidopsismentioning
confidence: 99%
“…However, further studies point to SYN3 acting as a significant player during female meiosis [Yuan et al, 2012]. In SYN3 RNAi plants, male gametogenesis is only slightly affected, with a marginal reduction in pollen viability [Yuan et al, 2012].…”
Section: Sex-specific Cohesins In Arabidopsismentioning
confidence: 99%